Características da carcaça e qualidade da carne de suínos de diferentes grupos genéticos - Fonseca, Patricia Alves Franco da (2016)
The demand for pork with sensory features that meet consumer demands, both for consumption in natura and processed products is relevant, therefore, evaluated the effect of different genetic groups of pigs slaughtered at two different weights (100 and 120 kg liveweight) regarding the quality of carcass and meat. The experiment with the participation of forty-eight animals, which are three distinct genetic groups: animals belonging to the genetic group 1 (G1) with 50% Duroc, Landrace and 25% 25% Large White; genetic group 2 (G2) with 29.7% Duroc, 29.7% Large White, Landrace 25% and 15.6% Pietrain and genetic group 3 (G3) with 29.7% Duroc, Landrace 25%, 17.2 % Large White, Pietrain 15.6% and 12.5% Moura. They collected data gain of daily weight (ADG), being slaughtered as reached the stipulated weight. After the slaughter, the characterization was carried out: hot carcass yield (WHR), cold carcass yield (RCF), ribeye area (REA), backfat thickness (ET) and drip loss (PG) . For performance evaluations of major cuts, carcasses were split into its primary cuts: head, ham, loin, fillet, belly, ventral belly, skirt steak, palette, palette-on, tip of the chest and leg. Later, Shank was deployed in the following structures: topside, rump, hard cushion, duck, lizard, bone, internal fat, external fat, skin and bones, cuts to income assessment. During boning, was collected the Longíssimus dorsi muscle of each experimental unit for further physical and chemical analysis, the following determinations are made: pH, color, water holding capacity, TBARS (lipid oxidation test), fluid loss by cooking , cholesterol, shear force, chemical composition and fatty acid profile. Statistical analysis was performed using factorial design (3x2), and the data were analyzed with the aid of SAS software, version 9.1. The animals of Duroc strain showed higher carcass yield (WHR and RCF) and higher yield of some commercial cuts, as forearm and sobre-paleta, already Moura race, influenced positively the GPD, the amount of internal fat and yield head and fillet, but negatively on the PG. In the remaining meat quality assessments, the crosses did not differ. The slaughter weight at 120 kg liveweight showed higher ADG, RCF, WHR, AOL and increased income for some commercial cuts like flank steak and leg, however, influenced the higher deposition of external carcass fat and greater amount of cholesterol present in the muscle . While animals slaughtered at 100 kg presented more C18-1n9c (oleic), and monounsaturated fatty acids (MUFA) and some commercial cuts (forearm and topside). It follows that the use of Moura and Duroc breed industrial crossings, provide good carcass characteristics and meat quality as well as good animal. The slaughter of animals at 120 kg BW, proved to be an alternative to housing production with good high and muscular performance ADG of animals to slaughter.